Costs Analysis of Kidney Transplantation in Spain: Differences Between Regional Health Services - Lorena Agüero-Cobo; José Luis Cobo-Sánchez; Noelia Mancebo-Salas; Zulema Gancedo-González (Kidney and Dialysis, 2024)
Background: For our society, chronic kidney disease is a major public health problem associated with high mortality, morbidity, reduced quality of life and a progressive increase in health costs. The aim of this study was to analyze and compare the current cost of kidney transplantation (KT) and kidney–pancreas transplantation (KPT) among the different Regional Health Services (RHS) in Spain. Methods: A descriptive comparative study analyzing the public prices of RHS in Spain. The Official Gazette of the different communities was consulted, where the latest available order on this type of cost was sought. A descriptive analysis was made of the stipulated cost of the KT and KPT, for each degree of severity, RHS, year of publication and cost calculation method. Mean cost and standard deviation were calculated. Results: KT prices were found for 15 of the 18 RHS (83.33%). The average cost of KT in Spain was EUR 33,926.53 ± 6950.053 (range from EUR 23,140.37 in the Canary Islands to EUR 48,205.75 in Catalonia). For KPT, costs were found for 5 of the 18 RHS (27.8%). The mean cost of KPT was EUR 65,792.38 ± 11,273.12 (ranging from EUR 49,418.81 in Navarra to EUR 78,363.20 in Andalusia). Conclusions: There is a large variability in KT and KPT costs in Spain between RHS. Our study underlines the importance of adopting standardized and updated costing methods for KT and KPT.